Availability of opioid agonist treatment and critical incidents in Forensic Clinics for Dependency Diseases in Germany - Reiners, Sven; Opitz-Welke, Annette; Konrad, Norbert; Voulgaris, Alexander (Frontiers in Psychiatry, 2022)
BACKGROUND: Prevalence of substance use disorders, especially opioid use disorders, is high in patients admitted into forensic psychiatric settings. Opioid agonist treatment is a safe and effective treatment option for patients that suffer from opioid dependence. Surprisingly, data on the availability and practice of opioid agonist treatment (OAT) options in German Forensic Clinics for Dependency Diseases is rare. MATERIAL AND METHODS: We conducted an observational study on all forensic addiction treatment units in Germany (Sect. 64 of the German Criminal Code). A questionnaire on the availability and practice of OAT was sent to all Forensic Clinics for Dependency Diseases in Germany. We compared the forensic clinics that offered OAT with those that did not offer this treatment option. The data were analyzed descriptively. The two groups (OAT vs. Non-OAT institutions) were compared concerning the given variables by either using Fishers exact test (categorical variables), t-test (normally distributed metric variables), or Wilcoxon-test (metric variables not normally distributed). RESULTS: In total, 15 of 46 Forensic Clinics for Dependency Diseases participated in the study (33%). In total, 2483 patients were treated in the participating clinics, 18% were relocated into prison due to treatment termination, and 15% were discharged successfully in 2018. 275 critical incidents were reported. In seven clinics treating 1153 patients, an OAT was available. Regarding critical incidents and successful discharge, no differences were detected in the clinics with or without an OAT. In the clinics that offered an OAT, we found a significantly higher rate of treatment termination without success (p<0.007) in comparison to clinics without an OAT program. Ninety-nine patients received an OAT, and this treatment was discontinued in the clinics due to illegal drug abuse (57%), refusal to give a urine drug sample (71%), and cases where the OAT was given away to other patients (85%). CONCLUSION: In Forensic Clinics for Dependancy Diseases in Germany, OAT is not available in every institution and, thus, access is limited. Critical incidents such as violent behavior against staff/patients and escape are not uncommon. Standardization of evidence-based treatment options such as OAT is recommended.